Implemantation of Inquiry Learning Strategy in Base Microbiology Experiment on the Learning Material Optimation Growth Temperature in Order to Increase the Study Result and Activity of Students in Biology Education Program - Sayuti, Irda (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to apply the inquiry model in the lecture material for bacterial growth temperature optimization, as well as prove an increase in student learning outcomes after applying the inquiry learning model. The form of this research is classroom action research (CAR). This research was carried out in two cycles, with the stages of each cycle including planning, action, observation, and reflection activities. From the results of this study can be known the percentage of classical completeness from the pre-test, cycle I, and cycle II. In the first cycle pre-test, the average score of students reached 60.4. Furthermore in the post-test cycle I increased to 79.1. This means an increase of 19 points. Then in the pre-test cycle II the average grade reached 58.8. While the post-test cycle II increased to 76.4. This means an increase of 19 points. From this explanation it can be said that the application of inquiry learning models to improve learning outcomes of bacterial growth temperature optimization material can be said to be successful because, it can exceed the achievement indicator targets previously set, namely the average grade value â¥ 65.